Pengaruh Fungsi Anggaran dan Kinerja Panitia Kerja (Panja) terhadap Efektivitas Penyusunan Rancangan Peraturan Daerah (Ranperda) di Dewan Perwakilan Rakyat Daerah (DPRD) Kota Ambon - Selanno, Della Michelle; Sahetapy, Petronela; Selanno, Hendry (Jurnal Ilmiah Global Education, 2025)
This study aims to examine the influence of the DPRD budget function and the performance of the Working Committee (PANJA) on the effectiveness of Draft Regional Regulation (Ranperda) preparation in the Ambon City DPRD. The research employed a quantitative survey approach. The population consisted of DPRD members and PANJA members involved in Ranperda preparation. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results indicate that the DPRD budget function positively and significantly affects the effectiveness of Ranperda preparation (Sig. = 0.002), while PANJA performance has a positive and highly significant effect (Sig. < 0.001). Simultaneously, both independent variables significantly influence the effectiveness of Ranperda preparation (Sig. < 0.001), accounting for 78.2% of the dependent variable’s variance. These findings highlight that effective Ranperda preparation requires synergy between well-planned budgeting and professional technical execution by PANJA. The study implies the need to enhance DPRD members’ capacity in budgeting functions, optimize PANJA performance through training and evaluation, and ensure intensive coordination between both parties to produce high-quality regional regulations that impact local development.